(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Maxillofacial fractures in adolescents present unique diagnostic and management challenges due to ongoing craniofacial growth and differences in injury mechanisms compared to adults. In Bangladesh, epidemiological data focusing specifically on the 12–17-year age group remain limited. Objective: To determine the pattern, etiology, and distribution of maxillofacial fractures among patients aged 12–17 years presenting to a tertiary care facility in Bangladesh. Methods: A prospective cohort study was conducted in the Department of Oral and Maxillofacial Surgery, Community-Based Medical College, Bangladesh, from January 2024 to December 2024 at the Private Chamber, Mymensingh Specialized Dental and Maxillofacial Centre, and Community-Based Medical College Hospital (CBMCHB), Bangladesh. Using purposive sampling, 35 adolescents aged 12–17 years with radiologically confirmed maxillofacial fractures were enrolled. Data on age, sex, etiology, fracture site, and associated injuries were collected. Analysis was performed using SPSS version 23.0. Results: Of 35 participants, 80.0% were male. Road traffic accidents caused 71.4% of fractures. The mandible was the most common fracture site (57.1%), followed by the zygomatic complex (22.9%) and maxilla (14.3%). Isolated fractures occurred in 68.6% of patients, while 31.4% had multiple fractures. Dentoalveolar injuries accompanied 31.4% of cases. No significant association was found between sex and fracture site (p=0.432) or between age group and etiology (p=0.287). Conclusion: Mandibular fractures secondary to road traffic accidents predominate among Bangladeshi adolescents aged 12–17 years in this tertiary care setting. Targeted preventive strategies, including helmet enforcement and adolescent road safety education, are warranted. Journal of Paediatric Surgeons of Bangladesh (2026) Vol. 17 (1): 37-41